If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12u-6u=6
We move all terms to the left:
12u-6u-(6)=0
We add all the numbers together, and all the variables
6u-6=0
We move all terms containing u to the left, all other terms to the right
6u=6
u=6/6
u=1
| 9=x/20+10 | | -4(x+5)=-58 | | 3=3+k | | -3m-9=-m+7 | | 9x^2+48x-64=0 | | -7(k+10)+3k=11 | | -20=x/10 | | 42-3t=4t | | 6g=4+7g | | (x+3.02)^2=11.81 | | 5y+10=6y+7 | | -6p=-4-10p | | 4(x+2)-2=-17 | | 4(3x+3)=3x+27 | | 4x=1-9x=106 | | -8d+2=-40d+2 | | 4+-2=2x+9 | | 6t^2−13t+5=0 | | -8q=-10-6q | | 5p÷5=-25÷5 | | 10=4y+15-9y | | 14(8x-16)=1/2(8x-4) | | y÷12=10 | | 10x-50=15 | | -z=-3z+8 | | 3•n=2•9 | | m/9=3/5 | | g=-g+10 | | 20=-15r | | (2x/3)-x=x/15-4/5 | | 5x+5=5-10x | | n-3/2=8 |